The Effect Of Financial Performance On Pt Indofood Sukses Makmur, Tbk's Stock Price On The Indonesia Stock Exchange (Period Of 2016 – 2020) - Ahmad Ramdany; Tarida Marlin Surya Manurung (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
One of the financial instruments traded in the capital market is shares. Shares can be defined as signs of participation or ownership of a person or entity in a company or limited liability company. This study was conducted to examine the effect of financial performance on stock prices as measured by the difference between the years of the establishment of a company and the year of research. The variable Gross Profit Margin (GPM) is gross profit with a comparison of net sales, cost of goods sold, and net sales. A Current Ratio (CR) is the current ratio between total current assets and total current liabilities. Net Profit Margin (NPM) is the net profit comparison between net profit and sales. The sample in this study is PT. Indofood Sukses Makmur, Tbk, which is listed on the Indonesian Stock Exchange for the period 2016-2020. This research uses a purposive sampling method. Hypothesis testing in this study uses Multiple Linear Regression Analysis. The results of hypothesis testing show that (1) gross profit margin (GPM) has an effect on stock prices. (2) Current Ratio (CR) has an effect on stock prices. (3) NPM has an effect on stock prices. (4) GPM, CR, and Net Profit Margin (NPM)) all have an impact on the share price. From the results of the Adjusted R Square test, it shows that the independent variables Gross Profit Margin, Current Ratio, and Net Profit Margin are able to influence the dependent variable of stock price by 94.4%. while the remaining 5.6% is explained by other variables not examined. Keywords: Gross Profit Margin, Current Ratio, Net Profit Margin and Stock Price. One of the financial instruments traded in the capital market is shares. Shares can be defined as signs of participation or ownership of a person or entity in a company or limited liability company. This study was conducted to examine the effect of financial performance on stock prices as measured by the difference between the years of the establishment of a company and the year of research. The variable Gross Profit Margin (GPM) is gross profit with a comparison of net sales, cost of goods sold, and net sales. A Current Ratio (CR) is the current ratio between total current assets and total current liabilities. Net Profit Margin (NPM) is the net profit comparison between net profit and sales. The sample in this study is PT. Indofood Sukses Makmur, Tbk, which is listed on the Indonesian Stock Exchange for the period 2016-2020. This research uses a purposive sampling method. Hypothesis testing in this study uses Multiple Linear Regression Analysis. The results of hypothesis testing show that (1) gross profit margin (GPM) has an effect on stock prices. (2) Current Ratio (CR) has an effect on stock prices. (3) NPM has an effect on stock prices. (4) GPM, CR, and Net Profit Margin (NPM)) all have an impact on the share price. From the results of the Adjusted R Square test, it shows that the independent variables Gross Profit Margin, Current Ratio, and Net Profit Margin are able to influence the dependent variable of stock price by 94.4%. while the remaining 5.6% is explained by other variables not examined. Keywords: Gross Profit Margin, Current Ratio, Net Profit Margin and Stock Price.